User Acceptability of Whole Exome Reproductive Carrier Testing for Consanguineous Couples in Australia. Issue 2 (14th December 2018) - Josephi‐Taylor, Sarah; Barlow‐Stewart, Kristine; Selvanathan, Arthavan; Roscioli, Tony; Bittles, Alan; Meiser, Bettina; Worgan, Lisa; Rajagopalan, Sulekha; Colley, Alison; Kirk, Edwin P.
Abstract: The study aimed to explore with consanguineous couples in Australia the acceptability and perceived utility of whole exome reproductive carrier screening for autosomal recessive and X‐linked recessive conditions. Semi‐structured interviews with 21 consanguineous couples were conducted prior to the offer of screening. Interviews were coded, and thematic analysis was informed by an inductive approach. Three major themes were identified: experiences and attitudes of Australian consanguineous couples, childhood genetic conditions and beliefs, and the perceived utility of genomic screening. All but one couple had previously sought genetic advice, and a large majority of couples were aware of childhood conditions within their family or community. Thirteen couples perceived consanguinity as increasing the risk of having affected children. Nine spoke of premarital screening programs routinely conducted in their countries of origin. All supported the concept and availability of genomic reproductive carrier screening. Hypothetically, if found to be carriers of a severe childhood disorder, 13 couples reported they would test a pregnancy, and 12 of whom would consider termination of pregnancy or pre‐implantation genetic diagnosis. Four couples would not test a pregnancy and two were unsure. A majority of couples would communicate potential at‐risk status to family members, although there were some caveats. Fourteen couples chose to have exome screening and reported that they would utilize the results with the goal of preventing childhood conditions. Of these couples, nine (64%) had an affected child but were aware that testing may reveal they were at risk for a child with a different condition and five (71%) without an affected child. While from diverse ethnic and backgrounds, all couples practiced a religion and all but one couple were recruited from the same clinical genetics unit, with a likely higher genetic literacy and bias towards accepting genetic testing. However, the choice made by all couples was reportedly made with consideration of their personal values, their current family situation, and exome testing issues, including fear of incidental findings and concerns about test reliability.